Designing Bangalore City for Human-Avian Coexistence: A Step Towards Including Non-Human Species in Design - Jathan, Shraddha; Rathish, Nikita (MAJ - Malaysia Architectural Journal, 2025)
For an ecosystem to function, there must be ongoing interactions between different species and their habitats, ways of life, and surroundings throughout their individual life cycles. However, Anthropocentric developments over the years have adversely affected the biodiversity of ecosystems across the globe. While certain species have adapted to urbanization and even benefit from living in proximity to humans (Synanthropes), some species today are at risk of endangerment. The human tendency to favour certain species selectively based on their aesthetic value puts the avians at a disadvantage. As a result, even though avians are an essential ecosystem component, they have a dearth of design inclusion in city planning. One of the nations with the fastest economic development, India is home to a wide variety of bird species, both resident and migratory. Bangalore, the city chosen for this study, is the centre of India’s high-tech industry known for its gardens and lakes. The garden city holds a vast population of different cultures, diversity, and services and houses many urban wildlife. It faces the consequences of rapid urbanization: overwhelming population, inadequate infrastructure, poor planning, and the possible threat of losing some of its native and migratory avian species. This study will focus on serving as a model for developing design recommendations for the cohabitation of Humans and Avians in Bangalore. The need for an interdisciplinary approach in design will be explored by understanding the natural and adaptive habitats & life cycles of avian species along with human-avian interactions (Conflicts, issues, and responses) to plan and reinvent the cities into being inclusive. The paper aims to establish a comprehensive framework to assist city planners in leveraging existing natural assets, such as gardens, green spaces, lakes, and infrastructure, alongside new construction projects to foster the creation of more vibrant and environmentally conscious cities.